Mid-infrared interferometric variability of DG Tauri: implications for the inner-disk structure - Varga, József; Dullemond, Cornelis (Arxiv, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics